2008
DOI: 10.1111/j.1542-4758.2008.00283.x
|View full text |Cite
|
Sign up to set email alerts
|

Central venous oxygen saturation and thoracic admittance during dialysis: New approaches to hemodynamic monitoring

Abstract: Intradialytic hypotension (IDH) is one of the most important short-term complications to hemodialysis (HD). Inadequate cardiac filling due to a reduction in the central blood volume is believed to be a major etiological factor. The aim of this study was to evaluate whether these pathophysiologic events are reflected in the central venous oxygen saturation (ScO(2)) and thoracic admittance (TA) during dialysis. Twenty ambulatory HD patients, 11 hypotension prone (HP) and 9 hypotension resistant, with central vas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“…Notably, mean ScvO 2 levels were already as low as 52.2% and 49.7% at the start of treatment in the respective groups. 26 An observational study with a follow-up of 36 months found a significantly higher mortality in patients with lower ScvO 2 , so that in an adjusted Cox analysis a 1 percent point decrease in mean ScvO 2 was associated with a 4% increase in mortality (hazard ratio 1.04 [95% confidence interval 1.01-1.08], P = .044). 27 Future studies should investigate whether changes in ScvO 2 during HD are also related to perfusion in vital organs, and whether this tool could potentially be used as an additional tool to guide KOOMAN ET AL.…”
Section: Whereasmentioning
confidence: 98%
See 1 more Smart Citation
“…Notably, mean ScvO 2 levels were already as low as 52.2% and 49.7% at the start of treatment in the respective groups. 26 An observational study with a follow-up of 36 months found a significantly higher mortality in patients with lower ScvO 2 , so that in an adjusted Cox analysis a 1 percent point decrease in mean ScvO 2 was associated with a 4% increase in mortality (hazard ratio 1.04 [95% confidence interval 1.01-1.08], P = .044). 27 Future studies should investigate whether changes in ScvO 2 during HD are also related to perfusion in vital organs, and whether this tool could potentially be used as an additional tool to guide KOOMAN ET AL.…”
Section: Whereasmentioning
confidence: 98%
“…In a study in 11 hypotension‐prone and 9 stable HD patients, ScvO 2 dropped by 7.7 ± 1.7% in hypotension‐prone patients, in contrast to a rise of 1.0 ± 1.3% in the latter group. Notably, mean ScvO 2 levels were already as low as 52.2% and 49.7% at the start of treatment in the respective groups . An observational study with a follow‐up of 36 months found a significantly higher mortality in patients with lower ScvO 2 , so that in an adjusted Cox analysis a 1 percent point decrease in mean ScvO 2 was associated with a 4% increase in mortality (hazard ratio 1.04 [95% confidence interval 1.01‐1.08], P = .044) …”
Section: Effects Of Circulatory Stress On Tissue Perfusionmentioning
confidence: 99%
“…In the only other study to examine ScvO 2 during HD, Cordtz et al [13] attempted to assess whether ScvO 2 could be used as a surrogate for cardiac output (as measured by thoracic impedance). More interestingly, the authors reported a much greater fall in ScvO 2 in hypotension-prone patients, without a close correlation with blood volume.…”
Section: Discussionmentioning
confidence: 99%
“…Correlations have been found between CBV and intradialytic hypotension. Cordtz et al have assessed CBV using thoracic admittance and cardiac function using central venous saturation [38]. They found that reduced baseline thoracic admittance was associated with intradialytic hypotension, and that the central venous saturation was reduced in these patients, suggesting a decrease in cardiac output.…”
Section: Discussionmentioning
confidence: 97%